Convergence of the Explicit Difference Scheme and the Binomial Tree Method for American Options (Journal of Computational Mathematics, 2004)
This paper is concerned with numerical methods for American option pricing. We employ numerical analysis and the notion of viscosity solution to show uniform convergence of the explicit difference scheme and the binomial tree method. We also prove the existence and convergence of the optimal exercise boundaries in the above approximations.
Keywords: American option; Explicit difference; Binomial tree method; Convergence; Numerical analysis; Viscosity solution.